Adolescent to young adult longitudinal development of subcortical volumes in two European sites with four waves - Backhausen, Lea L.; Fröhner, Juliane H.; Lemaître, Hervé; Artiges, Eric; Martinot, Marie-Laure Palillère; Herting, Megan M.; Sticca, Fabio; Banaschewski, Tobias; Barker, Gareth J.; Bokde, Arun L. W.; Desrivières, Sylvane; Flor, Herta; et al. (Human brain mapping, 2024)
Adolescent subcortical structural brain development might underlie psychopathological symptoms, which often emerge in adolescence. At the same time, sex differences exist in psychopathology, which might be mirrored in underlying sex differences in structural development. However, previous studies showed inconsistencies in subcortical trajectories and potential sex differences. Therefore, we aimed to investigate the subcortical structural trajectories and their sex differences across adolescence using for the first time a single cohort design, the same quality control procedure, software, and a general additive mixed modeling approach. We investigated two large European sites from ages 14 to 24 with 503 participants and 1408 total scans from France and Germany as part of the IMAGEN project including four waves of data acquisition. We found significantly larger volumes in males versus females in both sites and across all seven subcortical regions. Sex differences in age-related trajectories were observed across all regions in both sites. Our findings provide further evidence of sex differences in longitudinal adolescent brain development of subcortical regions and thus might eventually support the relationship of underlying brain development and different adolescent psychopathology in boys and girls.